Data work: A condition for integrations in health care - Bjørnstad, Camilla Hilda; Ellingsen, Gunnar (Health Informatics Journal, 2019)
Integration and interoperability between different information and communication technology (ICT) systems are crucial for efficient treatment and care in hospitals. In this article, we are particularly interested in the daily local work conducted by health-care personnel to maintain integrations. A principal aim of our article is, therefore, to contribute to a sociotechnical understanding of the “data work” that is embedded in the integration of health-care systems. Theoretically, we draw on the concepts of “information infrastructures” and “articulation work,” and we discuss how social status may influence the invisible articulation work. Furthermore, we show how historical decisions and existing systems both nationally and regionally have impacts on the daily work of local actors. Empirically, we have studied the formative stages of a large-scale electronic medication management system project in the Northern Norway Regional Health Authority.